Nephroprotective effects of cardamom essential oil (Amomum compactum Soland. Ex Maton) on kidney cells - Nisa Ul Hasanah; Ahmad Syauqy Tafrihani; Ummi Maryam Zulfin; Dhiya Ulhaq Salsabila; Ratih Kurnia Wardani; Muthi' Ikawati; Edy Meiyanto; Riris Istighfari Jenie (Indonesian Journal of Biotechnology, 2023)
Many chemotherapeutic agents cause various side effects, including nephrotoxicity. Cardamom essential oil (Amomum compactum Soland. ex Maton) contains compounds that exhibit antioxidant activity, such as 1,8‐cineole, α‐pinene, α‐terpineol, and linalool. This study focused on exploring the potency of cardamom essential oil (CEO) as an anti‐senescent induced by doxorubicin using the Vero kidney cell line. We first obtained the CEO by steam distillation, then evaluated its cytotoxicity using a trypan blue exclusion assay. Moreover, we performed senescence‐associated beta‐galactosidase (SA‐β‐gal) staining and 2’,7’‐dichlorodihydrofluorescein diacetate (DCFDA) staining to measure the effect of CEO on intracellular ROS level and cell senescence, respectively. Analysis of the compounds with gas chromatography‐mass spectrophotometry (GC‐MS) revealed seven compounds with significant abundance, namely 1,8‐cineole (50.82%), ß‐pinene (12.43%), α‐terpineol (8.50%), fenchone (4.10%), α‐pinene (4.00%), sabinene (3.00%), and linalool (1.98%). The cytotoxicity assay of CEO on Vero cells showed an IC50 value of 178 μg/mL. Thus, CEO is considered low cytotoxic for normal kidney cells (>100 μg/mL). Concentrations of 50 and 100 μg/mL CEO reduced the cell senescence induced by doxorubicin. Therefore, CEO has potency as a nephroprotective agent in doxorubicin‐induced senescence.